Chromatin accessibility and differentially expressed genes profiling in large yellow croaker (Larimichthys crocea) head kidney cells following iridovirus infection - Song, Chaowei; Huang, Ying; Han, Fang; Wang, Zhiyong (Frontiers in Immunology, 2025)
IntroductionThe large yellow croaker iridovirus (LYCIV) poses a significant threat to the aquaculture industry of Larimichthys crocea. Understanding the host defense response to LYCIV infection is crucial for developing effective strategies to mitigate its impact.MethodsIn this study, an epigenetic approach was employed to investigate dynamic changes in chromatin accessibility using the assay for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq). Additionally, RNA sequencing (RNA-seq) was used to analyze the expression pattern of immune response genes upon LYCIV infection.ResultsSubstantial alterations in chromatin accessibility were observed, particularly in the regulatory regions of key immune-related genes. Significant changes in the expression of AP-1 transcription factors, including the Batf gene, were noted. CUT&Tag results revealed that AP-1 was significantly enriched in the open chromatin regions of cytokine genes, with Batf potentially regulating the cytokine genes LIF and CLCF1.DiscussionThese findings suggest that AP-1 may play a crucial role in the defense response against viral infection by modulating inflammatory cytokines and contributing to cellular inflammatory responses. This study provides a comprehensive analysis of the epigenomic landscape and gene expression regulation during iridovirus infection in L. crocea, offering valuable insights for breeding programs aimed at combating iridovirus infections.